“Protección de los Activos Intangibles dentro del Derecho de Inversiones en Honduras” - Williams Cruz, Roberto Alejandro (2025)
This article examines the protection framework Honduras provides to investors holding intellectual property rights classified as “intangible assets.” In 2023 and 2024, Honduras faced multiple claims before ICSID for alleged violations of these rights. The analysis begins with a study of legal norms protecting Intellectual Property under Investment Law, as established in international treaties and national legislation. It then explores the role of key institutions ensuring this protection. Finally, it discusses the challenges investors face in securing privileged rights over their Intellectual Property or pursuing legal actions against infringements.